ANTI-SMOKING MESSAGES VERSUS PRO-SMOKING MESSAGES AMONG INDONESIAN ADOLESCENT SMOKERS - Megatsari, Hario; Damayanti, Rita; Kusuma, Dian; Ibad, Mursyidul; Nadhiroh, Siti Rahayu; Astutik, Erni; Sebayang, Susy Katikana (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2024)
Background: Anti-smoking messages (ASM) is a program designed to educate the public about the dangers of tobacco use, aiming to prevent adolescents and young people from smoking cigarettes in any form and to assist smokers in giving up their smoking habit. On the contrary, pro-smoking messages (PSM) is a marketing technique to promote tobacco products. Aims: This study was conducted to describe the exposure to ASM and PSM among Indonesian adolescent smokers (IAS). Methods: This study analyzed secondary data from the 2019 Global Youth Tobacco Survey (GYTS) Indonesia. The outcome variable was the respondent's smoking intensity in the last 30 days. The independent variables were the exposure to ASM and PSM in the various below-the-line media. Results: Most IAS were male (93.4%), mostly in secondary school (60.3%) and spent more than IDR 11,000 per week (71.1%). Adolescent smokers were exposed to ASM at a rate of 92.4%. Furthermore, ASM exposure happened to 60.5% of the low-intensity youth smoker group and 39.5% of the high-intensity youth smoker group. Meanwhile, 93% of adolescent smokers were exposed to PSM, with 40.8% in the high-intensity youth smoker group and 59.2% in the low-intensity youth smoker group.  Conclusion: The exposure to ASM and PSM in the adolescent smoker group was relatively the same. Keywords: ASM, PSM, prevention, public health, tobacco control, youth